Perception of sex workers of Lucknow City, Uttar Pradesh, India towards sexually transmitted infections - Pallavi Shukla; Jamal Masood; Jai Veer Singh; Vijay Kumar Singh; Abhishek Gupta; Krishna Asuri (Wolters Kluwer Medknow Publications, 2015)
The prevention, control, and management of sexually transmitted infections/reproductive tract infection (STI/RTI) are well-recognized cost-effective strategies for controlling the spread of human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS). A cross-sectional descriptive study was done over a period of 1 year to assess the prevalence of STI, knowledge level about STI, and the STI-HIV link among the female sex workers (FSWs) of Lucknow city, Uttar Pradesh, India along with their biosocial characteristics. Most of the FSWs were illiterate, married, Hindus, and belonged to general category. The prevalence rates of STI among street-based and home-based FSWs were 50.6% and 29.8%, respectively. Knowledge about the role of condom in prevention of STI and the STI-HIV link was significantly less among home-based FSWs than those who are street-based. There is a great lack in the awareness among FSWs regarding STI and their prevention. Behavior change communication (BCC) and advocacy strategy were developed, especially for the home-based group, to strengthen their knowledge regarding the STI-HIV link.